Pengaruh Lingkungan Sosial dan Digital Payment terhadap Pengelolaan Keuangan Mahasiswa STIE Surakarta - Jesisca Amanda Prihana; Dianing Widya Kusumastuti (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of digital technology has revolutionized the way people conduct transactions, including university students. Digital payment, as one of the most widely used innovations, enables cashless transactions through e-wallet applications that provide convenience, promotions, and cashback. Beyond technology, the social environment also plays a crucial role in students’ financial management, as peers, families, and communities can influence spending behavior. This study aims to analyze the influence of digital payment and social environment on the financial management of STIE Surakarta students. The research employed a quantitative method with a survey approach. The sample consisted of students who actively use digital payment, and data were collected through questionnaires. Multiple linear regression analysis was applied to examine the effect of each variable on financial management. The findings reveal that both digital payment and social environment have a positive and significant effect on students’ financial management. This indicates that students are not only motivated by the convenience of digital transactions but also by social interactions that shape spending behavior and financial management. The use of digital payment combined with social awareness helps students budget expenses, monitor income, and reduce wasteful behavior. In conclusion, understanding how digital payment is utilized and how it is influenced by the social environment can support students in creating more effective budgets, maintaining income records, and improving personal financial control. Furthermore, the results of this study provide valuable insights for digital payment providers in developing programs that assist students in managing their finances.